Education and science: current trends - Batanov M. S., Kirishchiev O. R., Zaitseva O. P., Montoeva M. A., Golubchikova M. G., Mironova T. P., Senognoeva N. A., Radina O. I., Osovtsev V. A., Serdiuk R. I., Iarosh O. N., Lebedeva E. N., Osovsky O. E., Kirzhaeva V. P., Kovrov V. V. (Education and science: current trends, 2017)
the article deals with issues related to ensuring the quality of the educational process in the system of higher professional education. The methodology and technology of a point-rating evaluation of the training session with students at the university is substantiated in the process of organizational and methodical activities for the control of the educational process at the faculty of the university. The article presents the “Technological map of the analysis of the training session” and justifies the technology of the score-rating evaluation of the training session in the system of higher professional education.
Keywords: качество образования; высшее профессиональное образование; методика преподавания; образовательный процесс в вузе; quality of education; профессиональная педагогическая деятельность; оценка образовательного процесса; оценка учебной деятельности преподавателя; обученность студентов; технология оценки труда педагога; балльно-рейтинговая оценка занятия; higher professional education; professional educational activities; educational process at the university; evaluation of the educational process; evaluation of teacher’s educational activity; students’ training; teaching method; teacher’s job evaluation technology; grade-rating evaluation of the lesson